Anatomy of non-tariff barriers in India–Sri Lanka free trade agreement: An empirical investigation - Pal, Barun Deb; Pohit, Sanjib (SAGE Publications, 2020)
This article attempts to answer one crucial research question: why the utilization of India–Sri Lanka Free Trade Agreement (ISFTA) route for trade is very poor by the Indian exporters (13%) as compared to their Sri Lankan counterpart (65%) even after one decade of its implementation? The available studies have blamed the non-tariff barriers (NTBs) which are hamstringing the growth of trade between these partners development of international trade. However, these have considered NTBs as subset of non-tariff measures (NTMs) which are quite narrow sense of finding the hidden barriers within the International trade process. Therefore, this article has analysed in detail the logistic process involved in international trade between India and Sri Lanka to understand various NTBs sheltered within this logistic process. Further, the article has identified issues which are not directly beyond the logistic process which are affecting the international trade between these two countries.JEL: F0, F1